Analysis of baculovirus spodoptera virulence in fall armyworm fed with cassava leaves - Eduardo Costa Paiva, Carlos; Romário de Carvalho, José; Contarini Machado, Lorena; Bolsoni Zago, Hugo; Hercos Valicente, Fernando; José Gonçalves dos Santos Junior, Hugo (Comunicata Scientiae, 2021)
The fall armyworm, Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae) is considered the main pest of corn (Zea mays L.) in Brazil and feeds on several other plant species, including cassava (Manihot esculenta Crantz). The food substrate influences the control efficiency of baculovirus and there aren’t studies on the effects of the application of baculovirus Spodoptera frugiperda multiple nucleopolyhedrovirus (SfMNPV) on cassava leaves in the mortality of S. frugiperda larvae. The main objectives of this study were to evaluate the efficiency of SfMNPV isolate 6 on S. frugiperda larvae fed on corn and cassava leaves. The food substrates were treated with three baculovirus concentrations (2 x 105, 2 x 106 and 2 x 107 OB mL-1) of a semipurified suspension, and of a commercial formulation (CartuchoVit®), both containing SfMNPV isolate 6, and then were offer to S. frugiperda second instar larvae. The semipurified virus was more virulent than the commercial formulation, regardless of the food substrate provided to insects, when concentrations of 2 x 105 and 2 x 106 OB mL-1 were used. However, there was no difference between treatments when baculovirus suspension of 2 x 107 OB mL-1 was use and the mortality rates were higher than 91%. The mortality was higher when the larvae fed on cassava leaves treated with SfMNPV. Therefore, the food substrate increased the efficiency of SfMNPV, which promises the use of this virus in the management of S. frugiperda in cassava crops.